Legal Oversight in Digital Marketplaces: A Bibliometric Analysis and Systematic Literature Review of Research Trends and Gaps - Muthoifin Muthoifin; Mariam Elbanna; Ishmah Afiyah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2026)
The regulation of digital marketplaces has emerged as a critical area of legal and economic inquiry as online platforms increasingly shape global commerce, consumer behavior, and competitive market structures. Despite this rapid growth, legal oversight of digital marketplaces remains fragmented and inconsistent across jurisdictions, creating significant challenges in understanding how existing legal frameworks respond to evolving digital economic activities. To address this gap, this study employs an integrated methodological approach combining bibliometric analysis and a PRISMA-guided Systematic Literature Review (SLR). The first phase involves bibliometric mapping using VOSviewer to identify the most productive countries, journals, authors, institutions, and frequently occurring keywords in research on digital marketplace regulation. This analysis provides a macro-level overview of the intellectual structure and development of legal scholarship in digital economic governance. The second phase consists of a systematic review of ten carefully selected scholarly articles, examining key legal issues, regulatory mechanisms, and emerging challenges associated with digital marketplaces. The findings reveal five major themes: consumer protection, platform accountability, algorithmic transparency, cross-border regulation, and data-driven market governance. The review further highlights persistent regulatory challenges, including fragmented legal frameworks, limited cross-border regulatory coordination, weak enforcement mechanisms, and insufficient oversight of algorithmic decision-making processes. The study’s primary contribution lies in integrating bibliometric analysis with systematic literature review methods to provide a comprehensive understanding of research trends, intellectual developments, and critical regulatory gaps in the legal governance of digital marketplaces.